Why ethics? On the constitution of the responsible human being along the lines of Paul Ricoeur’s thought - Mardones, José María (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The simple question «why ethics?» ends up in the complex problem of the constitution of the responsible human being. Fundamentally following the indications of Paul Ricoeur we address, by traversing the anthropological turn, the peculiarity of human beings who have to realize their freedom with others and in an institutional framework. This provides the steps for a reflection on the reasons for and the necessity of ethics.